Corticosteroid Effect in Acute Spinal Cord Injury in the Rural Area - Amir, Muhammad Rafif; Mahartha, Gde Rastu Adi (Journal of Medicine and Health Technology, 2024)
Spinal cord injuries (SCI) are devastating traumatic events in the lives of patients, often resulting in severe and/or permanent neurologic disabilities. Nearly half a million people are living permanently disabled in the United States due to traumatic SCI and 12,000–15,000 patients per year incur new injuries. A 78-year-old male patient came to the emergency room with a history of falling from a height with a pelvic position below exposed to trees 30 hours before admission, found weakness in the lower limbs, unable to urinate since yesterday. On radiologic examination, a burst fracture was found in the collumna of the 1st lumbar vertebra. The patient could not be examined for MRI due to limitations and unavailability of equipment at the hospital. The patient was given high dose of Methylprednisolone treatment for 3 days and there was no motoric improvement in the patient. Acute spinal cord injury is a very dangerous disease because it can cause patients both psychological and non psychological disorders. In areas that are left behind and do not have very good facilities and medical personnel to carry out this treatment. There is no treatment option other than using corticosteroids. However, the effect of corticosteroids still needs to be further developed and researched.